2021
DOI: 10.1021/acs.joc.1c01756
|View full text |Cite
|
Sign up to set email alerts
|

Development of Kilogram-Scale Convergent Liquid-Phase Synthesis of Oligonucleotides

Abstract: Oligonucleotide drugs show promise to treat diseases afflicting millions of people. To address the need to manufacture large quantities of oligonucleotide therapeutics, the novel convergent liquid-phase synthesis has been developed for an 18-mer oligonucleotide drug candidate. Fragments containing tetra- and pentamers were synthesized and assembled into the 18-mer without column chromatography, which had a similar impurity profile to material made by standard solid-phase oligonucleotide synthesis. Two of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…In fact, the technology is still in the running-in phase, but it promises to become a big innovation in terms of impact on the market of ON manufacturing and, consequently, on healthcare systems. 88 To reduce the impact of purification of standard linearlyassembled ONs on their overall greenness score, an interesting example of convergent LPS of a 18-mer ON has been recently reported by Zhou and co-workers 89 who demonstrated that a classical 54-reaction linear synthesis can be transformed in a synthetic approach based on 12 reactions and seven isolations (four cycles) involving soluble determinating groups (SDGs) which allow the fragment impurity profile to be simply monitored by high-performance liquid chromatography (HPLC) (Figure 19). As scope extension, they synthesized a gram-scale 34-mer ON with complete control on the impurity profile of fragments and proved that a final full-length ON with comparable purity to that reported for the corresponding SPOS could be obtained.…”
Section: Liquid-phase Tides Synthesis (Lpts)mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the technology is still in the running-in phase, but it promises to become a big innovation in terms of impact on the market of ON manufacturing and, consequently, on healthcare systems. 88 To reduce the impact of purification of standard linearlyassembled ONs on their overall greenness score, an interesting example of convergent LPS of a 18-mer ON has been recently reported by Zhou and co-workers 89 who demonstrated that a classical 54-reaction linear synthesis can be transformed in a synthetic approach based on 12 reactions and seven isolations (four cycles) involving soluble determinating groups (SDGs) which allow the fragment impurity profile to be simply monitored by high-performance liquid chromatography (HPLC) (Figure 19). As scope extension, they synthesized a gram-scale 34-mer ON with complete control on the impurity profile of fragments and proved that a final full-length ON with comparable purity to that reported for the corresponding SPOS could be obtained.…”
Section: Liquid-phase Tides Synthesis (Lpts)mentioning
confidence: 99%
“…To reduce the impact of purification of standard linearly-assembled ONs on their overall greenness score, an interesting example of convergent LPS of an 18-mer ON has been recently reported by Zhou and co-workers 89 who demonstrated that a classical 54-reaction linear synthesis can be transformed by a synthetic approach based on 12 reactions and seven isolations (four cycles) involving solubility determining groups (SDGs) which allow the fragment impurity profile to be simply monitored by high-performance liquid chromatography (HPLC) (Fig. 19).…”
Section: Liquid-phase Tides Synthesis (Lpts)mentioning
confidence: 99%
“…Longer sequences are also more challenging to resolve during chromatographic purification. Compared with linear chemical synthesis strategies, convergent biocatalytic approaches employing ligases should provide products in higher yield and overall purity and reduce the volume of acetonitrile required. , Ligases use ATP or NAD to activate an oligonucleotide fragment containing a 5′-monophosphate group (fragment 1) and then couples the resulting adenylated sequence to the 3′-OH of a second oligonucleotide fragment . GSK have developed an approach using DNA ligases, which involves annealing multiple fragments to a complementary DNA template to control the order of assembly (Figure a) .…”
Section: Oligonucleotidesmentioning
confidence: 99%
“…However, SPOS is generally not applicable to the manufacture of large‐scale oligonucleotide synthesis in terms of the cost, due to the large volume of excess reagents used and expensive specialized equipment settings. Solution‐phase oligonucleotide synthesis offers a valuable alternative for large‐scale synthesis because the reaction mixture is homogeneous, it provides unlimited scalability, and significantly reduces the need for excess reagents (Bonora, Biancotto, Maffini, & Scremin, 1993; Current Protocols article: Molina & Sanghvi, 2019; Zhou et al., 2022). An improved synthesis of the DNA dinucleotides such as pdCpA and pdCpdA has been reported that utilized typical oligonucleotide synthesis pathways such as coupling, oxidation, deprotection, and phosphorylation (Zhu & Scott, 2001).…”
Section: Commentarymentioning
confidence: 99%